1987
DOI: 10.1515/zna-1987-1212
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of the System LaCl3-CaCl2-NaCl

Abstract: The phase diagram of ternary system LaCl3-CaCl2-NaCl has been constructed from the phase diagrams of the three binary systems and of thirteen quasi-binary systems determined by DTA. For the binaries LaCl3-CaCl2 and CaCl2-NaCl eutectic points were observed at 651 °C , 35.1 mol% LaCl3 and at 508 °C , 49.9 mol% NaCl, respectively. For LaCl3-NaCl, a peritectic point besides the eutectic point at 545 °C , 36.1 mol% LaCl3 was found at 690 °C , 57.5 mol%, which is attributable to the formation of the peritectic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In contrast, the corresponding CN in solid LaCl 3 was 9, as described in [26]. This small difference in CN from 9 (solid) to 8.2 (melt) would be rather difficult to be explained from the large expansion in molar volume on melting, 19.1% [29] since the change of CN from 6 (solid) to 4.0-4.5 (melt) on melting of several alkali halides corresponded to the volume change of about 20%. There was also found a discrepancy between the results of XRD and XAFS concerning the coordination number of La-Cl pair.…”
Section: Xafsmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, the corresponding CN in solid LaCl 3 was 9, as described in [26]. This small difference in CN from 9 (solid) to 8.2 (melt) would be rather difficult to be explained from the large expansion in molar volume on melting, 19.1% [29] since the change of CN from 6 (solid) to 4.0-4.5 (melt) on melting of several alkali halides corresponded to the volume change of about 20%. There was also found a discrepancy between the results of XRD and XAFS concerning the coordination number of La-Cl pair.…”
Section: Xafsmentioning
confidence: 87%
“…From detailed investigation of the peak heights and half widths in Fig. 5, the local structure of solid LaCl 3 is found to be different from that at RT, giving decreases of coordination number (6.00 + 3.21 → 8.03) and interatomic distance (0.278 nm, 0.305 nm → 0.279 nm), implying the existence of another stable state in solid LaCl 3 before melting at 1150 K [28]. The decrease in coordination number for La-Cl pair from RT to 1173 K is thought to be due to the increase in molar volume and to be well interpreted by that on melting, for instance, 19.1% [29].…”
Section: Xafsmentioning
confidence: 94%
“…According to the unpublished work of Sun and Qiao [31] on molten salt phase diagram evaluation by pattern recognition, the existence of the compound LiNd 2 Cl 7 in the LiCl-NdCl 3 system was strongly supported. It is intriguing that the compound LiNd 2 Cl 7 reported by Kim and Okamoto [19] and Sun and Qiao [31] was not confirmed by XRD or even not detected by other experimental researchers [17,18,[20][21][22][23][24][25][26][27][28][29][30]. Two probable reasons may be provided: one is that the compound only exists in a very limited temperature range, the phase transition should have occurred during the quenching of the XRD sample.…”
Section: Introductionmentioning
confidence: 92%
“…The other one is that the amount and purity of melts (NdCl 3 , LiCl) in the sample affect the DTA and XRD measurement seriously. As a matter of fact, the measured liquidus line in the NdCl 3 -rich side as well as the reported melting temperature of pure NdCl 3 differed greatly between the different investigations [17][18][19][32][33][34][35][36][37]. The abnormal angle in the measured NdCl 3 -rich side liquidus line from Zhang et al [17] or the systematically lower temperatures reported by Igarashi and Mochinaga [18], respectively, should be related to the poor purity of samples, especially NdCl 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation